Influence of external stack pressure on the performance of Li-S pouch cell. (1st January 2022) - Schmidt, Florian; Korzhenko, Alexander; Härtel, Paul; Reuter, Florian S; Ehrling, Sebastian; Dörfler, Susanne; Abendroth, Thomas; Althues, Holger; Kaskel, Stefan
Abstract: The lithium-sulfur (Li-S) cell system is promising to satisfy the increasing need for cost-efficient energy storage with high theoretical energies due to the enormous theoretical gravimetrical capacity and the abundance of sulfur. Furthermore, the technology readiness level of Li-S batteries increased steadily in recent years due to extensive research, as well as the number of reported prototype cells. However, an often ignored test parameter is the application of external pressure to the cell stack. In this study, the influence of external pressure on the performance of Li-S cells is investigated. Therefore, five-layered pouch cells with solvent-free processed cathodes are assembled. These cells are tested under lean electrolyte conditions (electrolyte to sulfur ratio of 4.5 µ l mg(S) −1 ). To evaluate the influence of the used electrolyte system either the state-of-the-art 1, 2-dimethoxyethane/1, 3-dioxolane electrolyte or the sparing polysulfide solvating hexyl methyl ether/1, 3-dioxolane electrolyte is deployed. The impact of pressure application is evaluated electrochemically as well as by post-mortem focused ion beam-scanning electron microscopy of the cycled electrodes. Moreover, a technique for infiltration of sulfur into the carbon host matrix is presented, discussed, and successfully implemented.